2020
DOI: 10.7202/1072643ar
|View full text |Cite
|
Sign up to set email alerts
|

When Local Meets Global: How Introducing English Destabilizes Translanguaging Practices in a Cross-Border Organization

Abstract: T he diversification of direct investment flows and its rebalance in favor of emerging markets increase the heterogeneity of local environments for multinationals (Jaussaud and Mayrhofer, 2014). This situation raises the question of global players accounting for local specificities and calls for a new understanding of the relationships between global and local dynamics (Mayrhofer and Very, 2013). With this perspective, one should view multinational companies (MNCs) as sites where global and local dynamics co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Here, proficiency does not equate with 'perfect grammar, an authentic accent, or extensive vocabulary' (Nurmi & Koroma, 2020, p. 8). In MNCs, pluri-lingual competence often manifests itself in practices such as code-switching, that is, 'shifting between languages during interaction' (Ahmad & Barner-Rasmussen, 2019, p. 2); 'translanguaging' (García & Wei, 2014;Langinier & Ehrhart, 2020), that is, using a mixture of languages (Janssens & Steyaert, 2014), and hybrid language use, such as parallel use of various national languages or company/professional jargon (Gaibrois, 2018).…”
Section: A Framework For Managing Linguistic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Here, proficiency does not equate with 'perfect grammar, an authentic accent, or extensive vocabulary' (Nurmi & Koroma, 2020, p. 8). In MNCs, pluri-lingual competence often manifests itself in practices such as code-switching, that is, 'shifting between languages during interaction' (Ahmad & Barner-Rasmussen, 2019, p. 2); 'translanguaging' (García & Wei, 2014;Langinier & Ehrhart, 2020), that is, using a mixture of languages (Janssens & Steyaert, 2014), and hybrid language use, such as parallel use of various national languages or company/professional jargon (Gaibrois, 2018).…”
Section: A Framework For Managing Linguistic Diversitymentioning
confidence: 99%
“…Here, proficiency does not equate with ‘perfect grammar, an authentic accent, or extensive vocabulary’ (Nurmi & Koroma, 2020, p. 8). In MNCs, pluri‐lingual competence often manifests itself in practices such as code‐switching, that is, ‘shifting between languages during interaction’ (Ahmad & Barner‐Rasmussen, 2019, p. 2); ‘translanguaging’ (García & Wei, 2014; Langinier & Ehrhart, 2020), that is, using a mixture of languages (Janssens & Steyaert, 2014), and hybrid language use, such as parallel use of various national languages or company/professional jargon (Gaibrois, 2018). In some contexts, such as multinational teams of IT engineers, shared pluri‐lingual competence and familiarity with technical and organisational jargon, can lead to the creation of ‘new languages’ by the given work group, thus helping staff feel more at ease in interactions and increasing their participation and voice (Gaibrois, 2019, p. 99).…”
Section: Implementing the Edi Agenda: The Illustrative Case Of Lingui...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research on individual exchanges in multilingual settings (Kramsch and Whiteside, 2008) has revealed how language choice emerges from the subjective perception of shifting power dynamics within interactions across different space and time scales. This has enriched scholarly understanding of how power relations influence these practices (Vaara et al, 2005), the impact of a subsidiary context on language practices (Harzing and Pudelko, 2013), or the joint influence of the geographical location and the corporate environment (Langinier and Ehrhart, 2020). Studies from multinational and cross-border companies have also demonstrated that employees can successfully challenge official language regimes they perceive as unfair or unfavourable (Nekula and Marx, 2014; Trépos et al, 2016).…”
Section: Previous Research and Theorymentioning
confidence: 99%
“…While the concern with standardised or ‘native’ language can be observed in various cultural contexts (Gunnarsson, 2014; Wilmot et al, 2023), it is not universal. This is particularly evident in multilingual work environments (Detzen and Loehlein, 2018; Langinier and Ehrhart, 2020) and teams employing English as a shared lingua franca (Nurmi and Koroma, 2020). Previous research within the unit under investigation highlighted that non-standard language use in internal communication was perceived as an integral aspect of life in the multilingual environment (Lovrits, 2022).…”
Section: Previous Research and Theorymentioning
confidence: 99%